Counseling of Osing: a Counseling Based on Local Wisdom Represented in Lontar Yusuf Manuscript - Rofiq, Arif Ainur; Mustaqim, Muhamad; Hamid, Abdulloh (ADDIN, 2020)
Counseling has been a need for people all over the world to the present day. This article will discuss discourses and practices of counseling in Osing as illustrated in Lontar Yusuf Manuscript. The study applies a qualitative approach with the technique of content analysis. This article argues that counseling has not only been a dominant discourse and practice of the modern society in the West but also a cultural wealth in the traditional society in Indonesia, as can be seen in Banyuwangi people (Osing). This article further argues that traditional local values of Osing—such as moco saloko (passing on God’s teachings through songs), ngedapteyan (being aware, patient, and resilient), angering sang putri (relieving sorrow), and munajah (praying to God)—has been a foundation for discourses and practices of Osing which can develop awareness of basic concepts of counseling and therapeutic techniques based on the importance of religion and godliness. The result of this study shows that counseling based on local wisdom of Osing can contribute to enrich discourse and practices of counseling in the modern era.